MODERNISASI PENDIDIKAN ISLAM INDONESIA PERKEMBANGAN KURIKULUM MADRASAH SERTA DAMPAK POSITIF DAN NEGATIFNYA - Muhammad Arifin Ritonga (Pascasarjana UIN Sumatera Utara, 2021)
Madrasas are religious-based educational institutions that have long existed in Indonesia that seek to actively develop the potential in students to have life skills with spiritual, intellectual, emotional intelligence and noble character, as well as all skills that may need in society. Nation and state. The development of the madrasa curriculum in Indonesia is inseparable from the early history of converting to Islam and its development since pre-independence times. In general, the madrasa curriculum has different variations depending on the situation and conditions in various places. From pre-independence until the current reform era, Madrasas, one of the Islamic educational institutions, have experienced various curriculum development. Both in the form of a total change from before or only limited to edits for improvement..